Evaluation of Industrial Hygiene and Ergonomics and Their Effects on Worker Fatigue in Printing Services Using the 10-Beat Method - Putri, Deswita Amelia; Unzila, Fitri; Nur, Amelia; Munthe , Sahara (The Future of Education Journal, 2026)
The evaluation of industrial hygiene and ergonomic conditions is essential to understand their effects on worker fatigue, particularly in printing services characterized by repetitive tasks and prolonged sitting postures. This study aimed to evaluate industrial hygiene and work ergonomics and analyze their effects on worker fatigue in printing services using the 10-beat method. A descriptive observational approach was applied through direct workplace observation, environmental measurements, and heart rate assessment before and after work as an indicator of physiological workload.The results showed that industrial hygiene conditions were suboptimal, indicated by a workplace temperature of approximately 30°C, limited ventilation, and insufficient lighting. Ergonomic evaluation revealed non-ergonomic workstations that encouraged forward-bending sitting postures. Heart rate measurements increased from 13 beats per 10 seconds before work to 19 beats per 10 seconds after work, reflecting a light to moderate level of worker fatigue.In conclusion, inadequate industrial hygiene and ergonomic conditions were found to have measurable effects on worker fatigue. Improvements in ergonomic workstation design and environmental control are necessary to reduce fatigue and support occupational health in printing services.